(untitled) (Journal of Engineering, 2010)
This paper include study of CO and NOx emissions exhausted from single cylinder, 4-stroke S.I. engine, Ricardo E6, with variable compression ratio, spark timing and equivalence ratio, worked by supplementary hydrogen to gasoline. The speed of 25 rps and higher useful compression ratio (HUCR) were chosen in studying the effect of wide range of equivalence ratios and spark timing on CO and NOx emissions submitted from engine. The study showed that exhaust gas emissions depend mainly on equivalence ratio. The higher value of NOx concentrations was in lean side near the stoichiometric equivalence ratio, and reduced when getting far from this ratio. CO concentrations were too small in the lean side, and the effect of equivalence ratio on it was too small in this side also, it increased in the rich side. It was observed that retarding spark timing reduces the NOx concentrations by a large percentage; there was no effect of spark timing on CO concentrations. The effect of speed on NOx concentrations was studied, and it was observed that these emissions became higher at medium speeds and reduced in higher and low speeds, CO concentrations increased with increasing speed also. NOx concentrations increased with increasing hydrogen volumetric ratio in mixture while CO concentrations reduced by this increase.